Are we Training Future Physicians with Critical Thinking? A Cross-sectional Study Measuring Disposition Towards Critical Thinking among Medical Students - Ali Zain, Tariq Iqbal, Aisha Hameed, Muhammad Maqsood, Ali Shakeel, Sadia Yaseen, Noor Fatima, Umar Farooq Dar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: To be a lifelong learner, critical thinking is an essential skill for medical students. Measuring disposition towards critical thinking is needed to evaluate the effectiveness of the ongoing changes in curriculum and syllabus of medical colleges. Objective: To determine the disposition towards critical thinking among medical students at a public sector College in Pakistan. Methodology: This cross-sectional study was carried out at Gujranwala Medical College Gujranwala from 1st April 2023 to 30th September 2023 and 197 medical undergraduate students were enrolled. The disposition towards critical thinking was measured in two dimensions i.e. critical openness and reflective skepticism using a prevalidated, open source, self-administered critical thinking disposition scale (CTDS) short form. This tool contains eleven statements to be answered on a scale of one to five ranging from strongly disagreement to strongly agree with neutral in between. A score greater than 44 was labelled as high, between 35 to 44 as moderate and less than 35 as low score measuring disposition towards critical thinking. Results: 26.7% percent had high disposition towards critical thinking while 62% had moderate and 11.2 percent had very low score on critical thinking disposition inventory. Among the sampled population three fourth students were living in hostel, while one fourth were daily commuting to college. Academic performance was measured using marks in last high-stake exam. Ember lost high stake exams 30% students have more than 70% marks There was no significant association between academic performance in lost high stake exam and score in this position towards critical thinking (p=0.225). Conclusion: The disposition towards critical thinking among medical students is acceptable and current academic performance measures are not found associated with degree of disposition towards critical thinking. Keywords: Critical openness, Reflective skepticism, Disposition towards critical thinking